The Effectiveness of Development Planning of Civil Servants Apparatus in Improving Competence in 2019 - Muhammad Isa; Rasyidin Rasyidin; M Akmal (Malikussaleh Social and Political Reviews, 2020)
This study examines the effectiveness of the development planning of the state civil apparatus in increasing competence. The research objective is to understand how the planning for the development of the state civil apparatus in increasing competence by the Bener Meriah District Education and Training Personnel Board. The theoretical perspectives used are public administration theory, planning effectiveness theory, state civil servant resource management theory, and competency development. The research method used is qualitative. The results showed that planning for the development of the state civil apparatus in increasing competence by BKPP Bener Meriah Regency is still not effective, this can be seen from the indicators of planning effectiveness according to Cambel JP, including program success, target success, satisfaction with the program, levels of input and output and achievement of goals. all of which are still ineffective. Internal obstacles are due to the lack of budget for the education and training program so that they cannot provide competency development training for ASNs, and external obstacles are due to the lack of interest in ASNs to improve competence due to high training costs and lack of commitment from SKPK leaders in Bener Meriah Regency in motivating ASNs to improve their competence.